Effect of operational parameters and Pd/In catalyst in the reduction of nitrate using copper electrode. Issue 22 (17th November 2018) - Beltrame, Thiago Favarini; Coelho, Vanessa; Marder, Luciano; Ferreira, Jane Zoppas; Marchesini, Fernanda Albana; Bernardes, Andrea Moura
ABSTRACT: Water with high concentration of nitrate may cause damage to health and to the environment. This study investigated how concentration, current density, flow, pH, the use of Pd/In catalyst and operating mode (constant current density and constant cell potential) have an influence in the electrochemical reduction of nitrate and in the formation of gaseous compounds using copper electrode. Experiments were performed in two-compartment electrolytic cells separated by a cationic membrane with nitrate model solutions prepared as a surrogate of concentrated brines from membrane desalination plants. The results show that the electroreduction process has potential for reduction of nitrate and that it is influenced by the operational conditions. The best conditions found for the treatment – with satisfactory reduction of nitrate, formation of gaseous compounds and reproducibility – were at nitrate concentrations of 600 and 1000 mg L −1, current density of 1.1 mA cm −2 and without pH control, since in these conditions the production of gaseous compounds is higher than the production of nitrite. When Pd/In catalyst was used, the nitrate reduction was 50% after 6 h of experiment and the predominant product were gaseous compounds. When compared to the experiment without the catalyst, the arrangement with Pd/In was the most efficient one.